Variation of Politeness Strategies Among the English Education Students at Islamic Institute of Muhammadiyah Sinjai - Bahrun, St Rahmaniah; Putri , A. Mentari Nurul (JLE: Journal of Literate of English Education Study Program, 2020)
This study aims to find variations in the use of student politeness strategies in Islamic Institute of Muhammadiyah Sinjai. The researcher applied a descriptive qualitative research method. The participants of this research were 5th semester of English Education program consisting 34 students. The observation administered and mainly observed during the teaching and learning process in the classroom. The transcriptions were analyzed and discussed based on the theory of politeness of Brown and Levinson (1987). The findings from this study show that English students used different kinds of expressions to encode their politeness in the class. Those expressions were in the forms of greetings, thanking, addressing terms, apologizing, asking permission, rejecting, and fillers. There are also several terms comes from the student's regional language which is used as a form of their politeness. These expressions are categorized as positive and negative politeness.